Effect of ZrB2 on microstructural, mechanical and corrosion behaviour of aluminium (AA7178) alloy matrix composite prepared by the stir casting route. Issue 9 (1st May 2021) - Kumar, S. Dinesh; Ravichandran, M.; Jeevika, A.; Stalin, B.; Kailasanathan, C.; Karthick, A.
Abstract: The aim of this work is to develop a new class of aluminium alloy matrix composites (AAMCs) reinforced with different weight percentages of zirconium diboride (ZrB2 ) particles through the bottom pouring type stir casting process. The mechanical and corrosion behaviours of aluminium can be improved by the addition of ceramic particles. Mechanical behaviours and microstructure of the composites were studied. Homogeneous distribution of ZrB2 particles in the matrix was analysed using scanning electron microscope. The corrosion behaviour of the proposed composites was analysed by electrochemical assessments, such as polarization tests and AC impedance spectra. Prepared specimens are submerged inside aqueous sodium chloride (NaCl: 3.5%) solution. Corrosion potential, current, resistance of linear polarization, capacitance of double layer, resistance of charge transfer and resistance of corrosion in material were determined. From corrosion outcomes, we concluded that AA7178–ZrB2 metal matrix composite revealed higher corrosion resistance than AA7178. The rate of corrosion resistance, hardness, impact strength and tensile strength was augmented gradually by way of increasing weight per cent of ZrB2 particles in the AA7178 matrix. Hardness was improved by 26% and the ultimate tensile strength was improved by 15% for the inclusion of 10 wt% ZrB2 particles in the AA7178 matrix. Highlights: Aluminium alloy matrix composites reinforced with zirconium diboride particles were developed by stir casting process. Mechanical, corrosion behaviours and microstructure of the composites were studied. Homogeneous distribution of ZrB2 particles in aluminium alloy matrix was observed from scanning electron microscope. AA7178–ZrB2 metal matrix composite revealed higher corrosion resistance than aluminium alloy. Hardness and ultimate tensile strength was improved for the inclusion of ZrB2 particles in AA7178 matrix.